The Impact of Far-Red Light Supplementation on Hormonal Responses to Cold Acclimation in Barley - Ahres, Mohamed; Pálmai, Tamás; Gierczik, Krisztián; Dobrev, Petre; Vanková, Radomíra; Galiba, Gábor (Biomolecules, 2021)
Cold acclimation, the necessary prerequisite for promotion of freezing tolerance, is affected by both low temperature and enhanced far-red/red light (FR/R) ratio. The impact of FR supplementation to white light, created by artificial LED light sources, on the hormone levels, metabolism, and expression of the key hormone metabolism-related genes was determined in winter barley at moderate (15 °C) and low (5 °C) temperature. FR-enhanced freezing tolerance at 15 °C was associated with promotion of abscisic acid (ABA) levels, and accompanied by a moderate increase in indole-3-acetic acid (IAA) and cis-zeatin levels. The most prominent impact on the plants' freezing tolerance was found after FR pre-treatment at 15 °C (for 10 days) followed by cold treatment at FR supplementation (7 days). The response of ABA was diminished in comparison with white light treatment, probably due to the elevation of stress tolerance during FR pre-treatment. Jasmonic acid (JA) and salicylic acid (SA) were transiently reduced. When the plants were exposed directly to a combination of cold (5 °C) and FR supplementation, ABA increase was higher than in white light, and was associated with enhanced elevation of JA and, in the longer term (after 7 days), with IAA and cis-zeatin increase, which indicates a stronger stress response and better acclimation. Cold hardening was more efficient when FR light was applied in the early developmental stage of the barley plants (three-leaf stage, 18 days), rather than in later stages (28-days). The dynamics of the phytohormone changes are well supported by the expression profiles of the key hormone metabolism-related genes. This series of treatments serves as evidence for the close relationship between plant hormones, light quality, and low temperature at the beginning of cold acclimation. Besides the timing of the FR treatments, plant age also represents a key factor during light spectrum-dependent cold acclimation.
Keywords: ječmen (rod); Acclimatization; low R/FR ratio; frost-tolerance; listy rostlin; Indoleacetic Acids; Freezing; Plant Leaves; aklimatizace; polymerázová řetězová reakce s reverzní transkripcí; stanovení celkové genové exprese; Cold Temperature; Light; Reverse Transcriptase Polymerase Chain Reaction; barley; kyselina abscisová; Gene Expression Regulation, Plant; kyseliny indoloctové; regulace genové exprese u rostlin; LED lighting; phytohormones; Abscisic Acid; Hordeum; regulátory růstu rostlin; zmrazování; světlo; nízká teplota; Gene Expression Profiling; Plant Growth Regulators